Guide students to graduation with personalized technology. Issue 3 (May 2016) - Sutton, Halley
Abstract : ANAHEIM, CALIF. — How do you effectively usher large groups of students through your programs and to degree completion? Technology to help advise your students toward degree completion and inform them of their progress toward the degree is beneficial for the workload of the Registrar's Office and for your students. Dennis Geyer, university registrar at Sacramento State University; Jean Irving, university registrar at Chico State University; and Cem Sunata, university registrar at California Polytechnic State University at San Luis Obispo spoke during the Pacific Association of Collegiate Registrars and Admissions Officers annual conference about the three different tools their institutions use to help guide students to graduation.